Medical marijuana users in substance abuse treatment - Swartz Ronald (BMC, 2010)
Abstract Background The rise of authorized marijuana use in the U.S. means that many individuals are using cannabis as they concurrently engage in other forms of treatment, such as substance abuse counseling and psychotherapy. Clinical and legal decisions may be influenced by findings that suggest marijuana use during treatment serves as an obstacle to treatment success, compromises treatment integrity, or increases the prevalence or severity of relapse. In this paper, the author reviews the relationship between authorized marijuana use and substance abuse treatment utilizing data from a preliminary pilot study that, for the first time, uses a systematic methodology to collect data examining possible effects on treatment. Methods Data from the California Outcomes Measurement System (CalOMS) were compared for medical (authorized) marijuana users and non-marijuana users who were admitted to a public substance abuse treatment program in California. Behavioral and social treatment outcomes recorded by clinical staff at discharge and reported to the California Department of Alcohol and Drug Programs were assessed for both groups, which included a sample of 18 reported medical marijuana users. Results While the findings described here are preliminary and very limited due to the small sample size, the study demonstrates that questions about the relationship between medical marijuana use and involvement in drug treatment can be systematically evaluated. In this small sample, cannabis use did not seem to compromise substance abuse treatment amongst the medical marijuana using group, who (based on these preliminary data) fared equal to or better than non-medical marijuana users in several important outcome categories (e.g., treatment completion, criminal justice involvement, medical concerns). Conclusions This exploratory study suggests that medical marijuana is consistent with participation in other forms of drug treatment and may not adversely affect positive treatment outcomes. These findings call for more extensive sampling in future research to allow for more rigorous research on the growing population of medical marijuana users and non-marijuana users who are engaged in substance abuse treatment.